SAFETY OF INTRAVENOUS THROMBOLYSIS IN STROKE MIMICS - A 15-YEAR EXPERIENCE - Miladinović, Uroš; Mikulan, Rea; Jovanović, Dejana R.; Padjen, Visnja (Medical Research, 2025)
Introduction: The necessity of timely administration of intravenous thrombolysis (IVT) in the treatment of acute ischemic stroke may result in its administration in conditions that mimic stroke with their clinical presentation (stroke mimics). Aim: To assess the safety of IVT administration in stroke mimics. Material and methods: A retrospective study of 764 patients treated with IVT in the period 2006.-2021. at the Department of Emergency Neurology of the University Clinical Centre of Serbia was conducted. Results: From 764 stroke patients treated with IVT, the diagnosis of stroke mimics was established in 22 patients (2.9%). The average age of patients with stroke mimics was 49.1 ± 16.3 (min 26, max 86), and 55% of patients were female. The most frequent vascular risk factor in this group of patients was arterial hypertension (41%), followed by smoking (14%) and hypercholesterolemia (14%). In comparison with the control group of thrombolysed patients with stroke (matched according to sex and age) a trend towards a milder initial clinical deficit measured by NIHSS score was determined (5 vs. 9; p=0.05) in the stroke mimics group. Furthermore, a higher probability of favorable functional outcome (mRS 0-2) was registered (91 % vs. 55%, p=0.007). There was no statistically significant difference between the two groups regarding the death outcome (p=1.000). Symptomatic intracerebral hemorrhage was not registered in any patient in the stroke mimics group. Conclusion: The use of intravenous thrombolysis in acute conditions presenting with the clinical picture of acute ischemic stroke is safe for the patients.